THE ROLE OF ARTIFICIAL INTELLIGENCE IN PREDICTING CONSUMER BEHAVIOUR IN ONLINE RETAIL - Muslimakhon Shokirova, Shakhboz Sobirov (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Artificial Intelligence (AI) has emerged as a game-changer in predicting consumer behavior, particularly in the context of online retail. This paper examines how AI algorithms are used to analyze consumer data and predict buying patterns, improving decision-making for online retailers. By utilizing machine learning models and deep learning techniques, businesses can tailor their marketing strategies, optimize inventory management, and increase sales. The research includes an evaluation of AI applications in predicting purchasing decisions, customer preferences, and potential market trends. The paper also discusses ethical concerns related to data privacy and the risks of over-reliance on AI models.